HUBUNGAN AKTIVITAS BELAJAR KELOMPOK DENGAN HASIL BELAJAR MUATAN IPS SISWA KELAS IV SDN GUGUS 05 KALIJAGA KECAMATAN AIKMEL TAHUN PELAJARAN 2020/2021 - Wardani Wardani; Nurul Kemala Dewi; Nurhasanah Nurhasanah (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2022)
This study aims to determine the relationship between group learning activities and the learning outcomes of class IV social studies content at SDN Kalijaga cluster 05, Aikmel sub-district. This type of research is quantitative with a correlational study approach. The techniques used for data collection are questionnaires and documentation. The data obtained were processed using the Product Moment correlation analysis technique assisted by the SPSS version 16.0 for windows program. The sampling technique used is Simple Random Sampling. The population in this study were all fourth grade students at SDN Gugus 05, Aikmel District, while the samples were grade IV at SDN 1 Kalijaga Selatan, SDN 1 Kalijaga Timur, SDN 2 Kalijaga and class IV at SDN 3 Kalijaga. The results showed that the group learning activity score was 41.4 (high). While the complete value of student learning outcomes for social studies content is 89.6 (good). The results of the hypothesis test show that there is a significant relationship between group learning activities and students' social studies content learning outcomes as indicated by a sig (2-tailed) value of 0.001 <0.05 at a significance level of 5% with a Correlation Coefficient value of 0.399 (rcount)> 0 ,2027 (rtable). So it can be concluded that Ha is accepted and Ho is rejected, which means that there is a significant relationship between group learning activities and the learning outcomes of social studies content for students at SDN Cluster 05 Kalijaga, Aikmel District, for the 2020/2021 academic year. This means that the better the group learning activities carried out by the teacher, the better the students' learning outcomes. Keywords : Group Study Activities, Social Studies Content Learning Outcomes